2019
DOI: 10.1111/jce.13894
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre experience with the second‐generation subcutaneous implantable cardioverter defibrillator and the intermuscular two‐incision implantation technique

Abstract: Introduction:The recently developed second-generation subcutaneous implantable cardioverter defibrillator (S-ICD) and the intermuscular two-incision implantation technique demonstrate potential favorable features that reduce inappropriate shocks and complications. However, data concerning large patient populations are lacking.The aim of this multicentre prospective study was to evaluate the safety and outcome of second-generation S-ICD using the intermuscular two-incision technique in a large population study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…In our series, all patients tested were cardioverted with 65 J. This finding confirms a previous experience on the implantation of second‐generation S‐ICDs by means of the two‐incision inter‐muscular technique, and well compares with previous studies involving conventional subcutaneous implantation, in which cardioversion success ranged from 91.2% to 92.7% at 65 J …”
Section: Discussionsupporting
confidence: 89%
“…In our series, all patients tested were cardioverted with 65 J. This finding confirms a previous experience on the implantation of second‐generation S‐ICDs by means of the two‐incision inter‐muscular technique, and well compares with previous studies involving conventional subcutaneous implantation, in which cardioversion success ranged from 91.2% to 92.7% at 65 J …”
Section: Discussionsupporting
confidence: 89%
“…This approach shortens procedural time, does not increase implantation complications, and is rapidly growing in use. 18 , 23 , 28 The IAS rate using the 2-incision technique was still low enough to meet the study’s performance requirement. Although early postimplant IAS has been reported with the 2-incision technique, presumably because of air along the electrode tract, 29 other mechanisms to explain the higher rate of IAS associated with eliminating the sternal incision are likely involved.…”
Section: Discussionmentioning
confidence: 93%
“…IAS rates were not found to be significantly different between the two‐ and three‐incision groups in the Brouwer study, 7 and a low IAS rate of 2.8% was found over the 21‐month follow‐up in the Migliore study 12 . In contrast, IAS in the UNTOUCHED trial 10 recently demonstrated an association to 2IT, with 18 month rate of 4.9% versus the 2.5% in those patients implanted with 3IT.…”
Section: Discussionmentioning
confidence: 97%
“…However, infection numbers from this PAS study also reveal no statistical difference in infection of either device system. Migliore, et al 12 reports no device‐related infections in a study of 101 patients implanted with the 2IT and intermuscular implant, with an average follow‐up of 21 months.…”
Section: Discussionmentioning
confidence: 99%